Scoundrels, cads, and other great artists - Smith, Jeffrey K. (Rowman & Littlefield, 2020)
"Scoundrels, Cads, and Other Great Artists introduces people to great art by showing the more salacious side of the personal lives of great artists. The book not only tells the stories of twelve artists, but explores how to look at art and the separation between art and artist. This lively narrative is enhanced by over 100 full-color images"--
Keywords: Geschichte 1500-2000; Künstlerkult; Künstler; Verhalten; Persönlichkeit; Anekdote; Artists / Biography / Anecdotes; Deviant behavior / Anecdotes; Art appreciation; Artists; Deviant behavior; Anecdotes; Biographies; Biografie